Improving sustainability through digitalisation in reverse logistics - Sharon Cullinane; Michael Browne; Elisabeth Karlsson; Yingli Wang (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
Online purchases of clothes are increasing rapidly and with it, the number of returns. Return rates of clothing bought online can be up to 70%, involving high reverse logistics costs to retailers as well as sustainability costs to society. This paper seeks to illustrate how digitalisation can potentially decrease both such costs. The paper is based on a literature review and subsequent empirical research. Qualitative information was obtained through detailed interviews with key personnel and observations of the reverse logistics operations of five major clothing retailers and two major logistics companies in Sweden, carried out in Spring 2017. The research confirmed the importance to the retailers of reverse logistics and highlighted some of the environmental consequences of the reverse logistics operations. It also unveiled several areas where digitalisation could both reduce the number of returns made in the first place and improve the efficiency of the reverse logistics processes involved in dealing with returns. There is very little research on reverse logistics in the online clothing industry despite it being the single biggest sector of online purchases in practically every country in the world. This paper brings to light some of the little-considered issues involved as well as suggesting ways in which technology can improve the sustainability of such operations. Both elements are original. Most retailers are concerned about the costs and sustainability of their operations. By providing insights into how these can be reduced, management can make better informed decisions.
urn:nbn:de:gbv:830-88218114; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; reverse logistics; clothing returns; digitalisation; Sweden